Exploring Music Education Methods in Shanghai’s Specialized and General High Schools - Wang, Yangyi; Syafiq Md Salleh, Mohd (Journal of Theory and Practice in Education and Innovation, 2025)
This paper investigates the music education methods utilized in Shanghai’s specialized and general high schools, emphasizing curriculum content and structure, pedagogical strategies, and educational environments as key components. In specialized high schools, such as The Affiliated High School of Shanghai Conservatory of Music, the method prioritizes intensive training in performance skills and music theory, blending traditional Chinese and Western musical traditions to groom students for professional careers. Conversely, general high schools, exemplified by Shanghai Gezhi Middle School, adopt a holistic approach, integrating music education with cultural literacy and creative expression within a comprehensive curriculum. This comparative study reveals how these methods reflect distinct educational philosophies—technical mastery versus cultural enrichment—and influence the quality of musical instruction. By dissecting these elements, the paper offers insights into optimizing music education practices to meet diverse student needs, providing valuable implications for educators and policymakers in China’s dynamic educational context.